The new local bodies and the new Department of Agriculture and Technical Education and the development of the resources of Ireland - Dawson, Charles (Statistical and Social Inquiry Society of Ireland, 1900)
Two classes of bodies have been lately created by the present Government. One class by the Local Government Act of 1898, and the other by the Act which established the Department of Agriculture and Technical Instruction of 1899. By the first Act the government of the thirty-two counties of Ireland, and the various towns and villages they contain, has been handed over to the care of the Irish Councils elected by popular franchise. They have fiscal powers, and can levy taxes for certain purposes. It appears to me that we have here at last the opportunity afforded of practically developing the vast natural and industrial resources of the country, which, up to this, have only been written of and spoken of, but the theories of which have never been realised. This realisation is the work of the new bodies.
Read Tuesday, 24th April, 1900.
Keywords: Agricultural development; Industrial development; 314.15